KOMPARASI MODEL PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS DAERAH TEMPAT TINGGAL SEKITAR DENGAN BERBASIS KEMENDIKBUD UNTUK MENGUKUR HASIL BELAJAR SISWA KELAS 4 - Mulyani, Tri; ,, Mawardi; widi, krisma (Jurnal Karya Pendidikan Matematika, 2019)
This study aims to find out whether there is an increase in learning outcomes using integrated regional-based thematic models of residential areas compared to MoEC-based learning in 4th grade elementary school learning. The type of research used is real research (true experimental). The sample of this study was 4th grade students of SDN Pasekan 03 as an experimental group. The data analysis technique used the average difference test (t test). The normality of the experimental group was 0.449> 0.05 and the control group was 0.434.> 0.05, the two groups were normally distributed. The homogeneity of the experimental group and the control group was 0.855> 0.05, so the two groups were homogeneous. The results showed t count 1604 with a significance of 0.0115 <0.05, so Ha accepted means that the learning outcomes using area-based housing around higher than the Ministry of Education and Culture.